Designing Strategy Agent Link Using SWOT Analysis Based On Business Canvas Model Service Company: Indonesia Company Case Study - Eriza Nira Rismia; Bambang Syairudin; Fuad Achmadi (Institut Teknologi Sepuluh Nopember, 2019)
OJK (Financial Services Authority) in collaboration with Indonesia Bank issued smart services and Bank XYZ (Persero) Tbk issued Agent link which is a non-office financial transaction service and link agent is an extension of XYZ Bank and XYZ (Persero) Tbk Branch X. Total agency x in 2018 as many as 57 agents. And the performance of link agents built by Surabaya branch X office for its transaction is low compared to the branch office built by Surabaya area office. This research is conducted to analyze the strategies implemented to help increase transaction agent linkage in Surabaya X branch office using SWOT analysis based on Business Model Canvas to improve performance in terms of several aspects and for decision stage using QSPM and the result with (TAS) on external factors is greater than the internal factor TAS, that’s means the right strategy decision to improve performance of Agent Link on Bank XYZ is by extensification. method it is expected that the company can use it as a foothold in deciding policy or evaluation of improvement on company